Media Informasi Tentang Dampak Kecanduan Penggunaan Gadget dalam Upaya Membangun Generasi Muda yang Sehat dan Sejahtera - Saparwati, Mona; Trimawati Trimawati; Abdul Wahid; Ucta P (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
The growing use of smartphones among adolescents carries a high risk of addiction, which can negatively impact physical, mental, and social well-being. To address this issue, a community service program was implemented to conduct early detection of gadget addiction among high school students and provide educational health media to raise knowledge and awareness about excessive smartphone use. The program involved 240 students of SMA Negeri 1 Tuntang and was conducted in three stages: screening, development of educational materials, and health counseling. Screening used the short version of the Smartphone Addiction Scale and revealed that 90% of students were classified as addicted. Prior to counseling, 81.25% of students had low levels of knowledge regarding healthy gadget use, which significantly improved after the intervention, with 83.4% achieving high knowledge levels. Health counseling proved crucial in enhancing students’ understanding and promoting responsible smartphone habits. The program highlights the importance of collaborative efforts by schools, parents, and students to limit smartphone use, encourage physical activity, and foster face-to-face social interactions to support adolescent well-being.